Effect of product diversification on firm performance: a study on Tractors Malaysia Holdings Berhad / Norafiza Zukelfali (Faculty of Business and Management, 2007)
This research reveals the effect of product diversification on the performance of Tractors Malaysia Holdings Berhad from year 1996 to year 2005, in terms of accounting-based, market-based and value-based measures. The analysis is further conducted with an adjusted variable of assets utilization by the holdings to see its' influence onto the performance-diversity original direction effect. The purpose of the research is to identify the relationship between product diversification and the holdings performance, and to examine the relationship with assets utilization. Recommendations for the holdings to accelerate the performance with the diversification and fully utilized assets in the present operation are highlighted. There are also suggestions for future researchers and the government. The product diversification activities and the assets utilization efficiency level by the holdings with respect to the industry during the year of study are analysed to see their effects on the holding's performance. Data were collected from secondary sources and arranged according to the priority of need for the research. Raw data on the variables were analysed using SPSS application system (Statistical Package for Social Science) and interpreted into Chi-Square Tests and Regression output tables The empirical finding shows a positive linear relationship between product diversification and the firm performance even though previous research found out that the relationship is in quadratic form. The principal that related international diversification on related product outperformed international diversification on unrelated product is met. However using econometric modelling which is regression, it is found that there is no correlation existed between product diversification and firm performance with assets utilization.